HMGB1 in nervous system diseases: A common biomarker and potential therapeutic target - Mao, Di; Zheng, Yuan; Xu, Fenfen; Han, Xiao; Zhao, Hongyang (Frontiers in Neurology, 2022)
HMGB1 is an early inflammatory factor expressed in various cells including neurons and microglia. With the progress of research, neuroinflammation is believed to be involved in the pathogenesis of neurological diseases such as Parkinson's, epilepsy, and autism. The HMGB1/TLR4 axis has received increasing attention as a key promoter of neuroinflammation. This review discusses the possible mechanisms by which HMGB1 mediates Parkinson’s disease, Stroke, Traumatic brain injury, Epilepsy, Autism, Depression, Multiple Sclerosis and Amyotrophic Lateral Sclerosis. HMGB1-targeted therapy can inhibit blood-brain barrier disruption, inflammatory molecule expression, and improve neurological symptoms in different disease models. Therefore, HMGB1 may serve as a risk factor for the above-mentioned disease progression. Future research needs to further explore the underlying molecular mechanisms and clinical translation.